Two stage least square method for prediction financial investment and dividend. (March 2019) - Yuniningsih, Yuniningsih; Taufiq, Muhamad; Wuryani, Eni; Hidayat, Rahmat
Abstract: There are 3 financial decisions in Financial Management Science including funding, investment and dividends. This study aims to determine whether there is interdependence between investment and dividend variables. The research method used two stage least square (2SLS). This research uses two equations of investment and dividend. The result of the research on investment equation shows that dividend has no effect to investment. The result of the research on dividend equation also shows that investment has no effect on dividend. These results indicate that investment funding does not depend on internal equity but can come from external equity and external finance. Thus, even if the company performs dividend division, Investment is still performed.